BRCA-Associated Pancreatic Cancer: The Evolving Management - Leung, Keith; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer is one of the deadliest cancers. While BRCA-associated pancreatic cancers are uncommon, the distinctive phenotype of this malignancy may offer unique therapeutic targets. At the 2013 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium, a review of the characteristics and outcomes of one large case series (Abstract #278), however, did not reveal a benefit to first-line platinum chemotherapy in the treatment of advanced pancreatic cancer. In another study (Abstract #147), substantial responses were observed in both patients with BRCA2-associated pancreatic cancer treated with the poly-(ADP-ribose) polymerase (PARP) inhibitor ABT-888 (veliparib). We will review these abstracts and our current knowledge of the treatment for patients with BRCA-associated pancreatic cancer. In this group of patients, these new results continue to shape our understanding of this disease. Image: Tufts University School of Medicine. Boston, MA, USA.